Juvenile idiopathic inflammatory myopathies: A clinicopathological study with emphasis on muscle histology - Sundaram Challa; Monalisa Hui; Saumya Jakati; Megha Shantveer Uppin; Liza Rajasekhar; Meena Angamuthu Kannan; Lokesh Lingappa; Murthy Murali Krishna Jagarlapudi (Wolters Kluwer Medknow Publications, 2019)
Background: Juvenile idiopathic inflammatory myopathies (JIIM) are rare and heterogeneous. Subtype identification is important for treatment. Materials and Methods: Patients below 18 years diagnosed as idiopathic inflammatory myopathy (IIM) according to the Bohan and Peter criteria between January 2010 and May 2015 were evaluated with muscle biopsy in the four domains: muscle fiber, inflammation, connective tissue, and vascular, with basic panel of histochemical stains as per recommendations of the European Neuromuscular center (ENMC) workshop 2015. Immunohistochemistry with CD 31 was done to assess capillary density. Results: JIIM constituted 15.25% of IIM with juvenile dermatomyositis (JDM) being the most common subgroup (24/27) followed by juvenile overlap myositis (JOM) (3/27) in association with systemic lupus erythematosus (2) and systemic sclerosis (1). Muscle biopsy in JDM was characterized by perifascicular atrophy, necrosis, degeneration, and regeneration in all and the other features included perivascular inflammation (21), lymphoid aggregates (2), mitochondrial abnormalities (9), sarcoplasmic vacuoles (6), capillary dropout (5), capillary dilatation (6), and perimysial fibrosis (14). JOM was characterized by auto-antibodies and perivascular inflammation. Conclusion: JIIMs were rare and JDM was the most common subtype. Muscle biopsy evaluation as per ENMC criteria characterized the subgroups.